دور السلطة الوطنية المستقلة لإلنتخابات في الجزائر -  زبريي إســـــــــــــحاق  دراجــــــــــــــــــي أميمة (المسيلة, 2023)
تمثل السلطة الوطنية المستقلة لالنتخابات في الجزائر من أبرز اآلليات القانونية الجديدة التي تعمل على مراقبة واإلشراف على االنتخابات ، خاصة وأن النظام اإلنتخابي في الجزائر شهد أحادية في السلطة هو ما أدى إلى خروج الشعب إلى الشارع في حراك سلمي من أجل التغير، وبها جاءت السلطة المستقلة من أجل السهر على قيام إنتخابات نزيهة وشفافة . ّر ألول مرة تسمية " القانون العضوي رقم 70/91 السلطة المستقلة"، وزّ ودها المنشئ لها أَق بجملة من الضمانات التي تدعم استقاللها، سواء من الناحية العضوية أو الوظيفية، كما جاء األمر 79/19 الذي ينظم اإلنتخابات، كمما أن التعديل الدستوري لسنة 1717 أعطى ضمانات أكثر للسلطة، وتعد االنتخابات الرئاسية األخيرة 1791/91/91 التجربة األولى التي يمكن من خاللها تقييم مدى شفافيتها. Resume The Independent National Authority for Elections in Algeria is one of the most prominent new legal mechanisms that monitor and supervise elections, especially since the electoral system in Algeria witnessed unilateralism in power, which led to the people taking to the streets in a peaceful movement for change. To ensure fair and transparent elections. Organic Law No. 07/19 establishing it approved for the first time the designation of the “independent authority” and provided it with a set of guarantees that support its independence, whether in terms of membership or functionality, as stated in Order 01/21 that organizes elections, just as the constitutional amendment of 2020 gave guarantees More authority, and the recent presidential elections on 12/12/2019 are the first experience through which it is possible to assess the extent of its transparency.
Keywords: السلطة الوطنية المستقلة ل - الا نتخابات - الجزائر